ERAP1 Controls the Interaction of the Inhibitory Receptor KIR3DL1 With HLA-B51:01 by Affecting Natural Killer Cell Function - D’Amico, Silvia; D’Alicandro, Valerio; Compagnone, Mirco; Tempora, Patrizia; Guida, Giusy; Romania, Paolo; Lucarini, Valeria; Melaiu, Ombretta; Falco, Michela; Algeri, Mattia; Pende, Daniela; Cifaldi, Loredana; et al. (Frontiers in Immunology, 2021)
The endoplasmic reticulum aminopeptidase ERAP1 regulates innate and adaptive immune responses by trimming peptides for presentation by major histocompatibility complex (MHC) class I molecules. Previously, we have shown that genetic or pharmacological inhibition of ERAP1 on murine and human tumor cell lines perturbs the engagement of NK cell inhibitory receptors Ly49C/I and Killer-cell Immunoglobulin-like receptors (KIRs), respectively, by their specific ligands (MHC class I molecules), thus leading to NK cell killing. However, the effect of ERAP1 inhibition in tumor cells was highly variable, suggesting that its efficacy may depend on several factors, including MHC class I typing. To identify MHC class I alleles and KIRs that are more sensitive to ERAP1 inhibitiondepletion, we stably silenced ERAP1 expression in human HLA class I-negative B lymphoblastoid cell line 721.221 (referred to as 221) transfected with a panel of KIR ligands (i.e. HLA-B*51:01, -Cw3, -Cw4 and -Cw7), or HLA-A2 which does not bind any KIRas negative control, and tested their ability to induce NK cell degranulation and cytotoxicity. No change in HLA class I surface expression was detected in all 221 transfectant cells after ERAP1 depletioninhibition. In contrast, CD107a expression levels were significantly increased on NK cells stimulated with 221-B*51:01 cells lacking ERAP1, particularly in the KIR3DL1-positive NK cell subset. Consistently, loss genetic or pharmacological inhibition of ERAP1 impaired the recognition of HLA-B*51:01 by the YTS NK cell overexpressing KIR3DL1*001, suggesting that ERAP1 inhibition renders HLA-B51:01 molecules less eligible for binding to KIR3DL1. Overall, these results identify HLA-B*51:01/KIR3DL1 as one of the most susceptible combinations for ERAP1 inhibition, suggesting that individuals carrying HLA-B*51:01-like antigens HLA-Bw4 allotypes may be candidates for immunotherapy based on pharmacological inhibition of ERAP1.